The Aesthetic Surveillance of Performance Art by the Romanian Securitate in the 1970s and 1980s. Issue 3 (4th May 2021) - Preda, Caterina
Abstract: This article discusses the specific case of the surveillance by the Securitate, the Romanian secret police, of artists who engaged in performance art (body art, action art, live art) during the last two decades of Romanian communism. Building on Cristina Vătulescu's concept of 'police aesthetics' and Mogoș and Berkers's 'mechanisms of control', this article analyses the aesthetic surveillance by the Securitate and the different strategies to prevent problematic art it employed towards performance artists that ranged from control, to discouragement, and support given to complying artists. Through a close reading of the files by the Securitate of three artists, Alexandru Antik, Imre Baász, and Wanda Mihuleac, I show performance art was considered as having an 'interpretative' or 'hostile content' depending on the status inside the regime of the artist who practiced it.